Analiza ryzyka kadrowego w controllingu personalnym - Nowak, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper treats the human resources risk analysis conducted by the human resources controlling. The article presents the research which proves the correlation between the human resource management quality and the company's results and also the research which show the risk of strategic decision implementation which ¡¡merges from human resources of the company. The place of the human resource controlling in risk management is depicted. The information flow needed for the human resources risk analysis is shown. The main methods of the human resources risk analysis in the human resources controlling (structure analysis and indicator analysis) are enumerated and explained. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 264-271